Pengenalan dan Pemanfaatan Tanaman Sebagai Obat Kepada Masyarakat Gampong Limpok Kabupaten Aceh Besar - Abdullah Abdullah; Yuri Gagarin; Zulfikar Zulfikar; Cut Nurmaliah; Muhammad Rusdi; Durrah Hayati; Ulfa Hansri Ar Rasyid; Devi Syafrianti (Jurnal Penelitian Pendidikan IPA, 2023)
The use of medicinal plants in society has existed since ancient times as a method of traditional medicine. The general public often lacks adequate education and information about the correct and safe use of medicinal plants. This can result in incorrect use and higher health risks. The aim of this research is to carry out more in-depth scientific research, implement strict regulations, provide education to the public, and promote sustainable and responsible practices of using medicinal plants. This research was conducted in July, 2023 in Gampong (Village) Limpok, Aceh Besar District. Research using descriptive qualitative method. Community data collection by interview, observation and documentation methods. The results of the study can be concluded that there are 32 plant species from the inventory that have long been used by the Gampong Limpok community as medicinal plants. Despite the potential benefits, there are also challenges and barriers that can arise in the community use of medicinal plants.